2013
DOI: 10.3746/pnf.2013.18.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Compositions of Korean Wheat Cultivars

Abstract: Twenty-nine Korean wheat cultivars were analyzed for 8 important minerals (Cu, Fe, Mn, Zn, Ca, K, Mg and P) using Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES). A hierarchical cluster analysis (HCA) was applied to classify wheat cultivars, which has a similarity in mineral compositions. The concentration ranges of the micro-minerals Cu, Fe, Mn, and Zn: 0.12~0.71 mg/100 g, 2.89~5.89 mg/100 g, 1.65~4.48 mg/100 g, and 2.58~6.68 mg/100 g, respectively. The content ranges of the macro-minerals C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Moreover, manganese, iron, and zinc contents in FSD‐08 were 1.68 ± 0.04, 3.83 ± 0.40, and 3 ± 0.85 g/kg and copper content in Ujala‐16 was 0.16 ± 0.04 g/kg. The results are in line with the observation of Choi, Kang, Hyun, Lee, and Park () who reported that wheat contained calcium, phosphorus, magnesium, potassium, copper, zinc, manganese, and iron in range of 39.76, 357.02, 126.88, 346.64, 0.41, 5.05, 2.43, and 4.48 mg/100 g, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, manganese, iron, and zinc contents in FSD‐08 were 1.68 ± 0.04, 3.83 ± 0.40, and 3 ± 0.85 g/kg and copper content in Ujala‐16 was 0.16 ± 0.04 g/kg. The results are in line with the observation of Choi, Kang, Hyun, Lee, and Park () who reported that wheat contained calcium, phosphorus, magnesium, potassium, copper, zinc, manganese, and iron in range of 39.76, 357.02, 126.88, 346.64, 0.41, 5.05, 2.43, and 4.48 mg/100 g, respectively.…”
Section: Resultssupporting
confidence: 92%
“…The mineral content of the raw and treated flours, as well as the Mahewu were determined following the method outlined by Choi, Kang, Hyun, Lee, and Park (2013) with some modifications. Briefly, 1.0 g of sample was digested with equal amounts (10 mL) of nitric acid and hydrogen peroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic diversity is a key to the improvement of cereals using conventional plant‐breeding methods. The genetic variability can be used effectively for quality improvement in wheat breeding programs by the development of varieties with a high mineral profile . Generally, adapted wheat varieties have low iron concentration in grains as compared to non‐adapted germplasm .…”
Section: Introductionmentioning
confidence: 99%